Randomized controlled trial of high dose bolus versus continuous intravenous infusion pantoprazole as an adjunct therapy to therapeutic endoscopy in massive bleeding peptic ulcer - Yamada S. (2014)
Background: After therapeutic endoscopy is performed in high-risk patients with peptic ulcer bleeding, rebleeding occurs in about 25 to 30%. High dose intravenous proton pump inhibitors (PPI) have been recommended for the use in high-risk patients to prevent rebleeding following successful therapeutic endoscopy. Objective: Compare the efficacy between pantoprazole high dose bolus injections and continuous intravenous infusion to prevent rebleeding in peptic ulcer patients after initial hemostasis is achieved by the therapeutic endoscopy. Material and Method: A clinical block randomized control trial was conducted at Maharaj Nakorn Chiang Mai Hospital in massive peptic ulcer bleeding patients. All patients underwent endoscopic diagnosis and treatment within six hours of admission. Hemostasis was achieved by therapeutic endoscopy in 28 patients who received 80 mg pantoprazole as a loading dose before intervention. They were randomized into two groups. The first group was given a high dose of pantoprazole, 40 mg bolus injections twice daily for seven days (n = 13). The second group was given continuous intravenous infusion of pantoprazole, 8 mg per hour for the first three days, followed with a 40 mg bolus injection twice daily similar to the first group from day 4 until day 7 (n = 15). After the seventh day, both groups were given 20 mg of oral pantoprazole once daily for two months. The data was analyzed by Fisher's exact test to compare the frequency of rebleeding within seven days after therapeutic endoscopy. Results: The frequency of recurrent bleeding between the high dose pantoprazole bolus injection group and the continuous intravenous infusion group was not significantly different, 30.8% and 33.3% respectively (p = 1.0). Three patients in the high dose bolus group and five in the continuous infusion group underwent surgery (p = 0.68). There was no statistically significant difference between the two groups by volume of blood transfusion, length of hospital stay, or mortality. Conclusion: In the present study, both PPI drug administration methods showed an equally effective for massive peptic ulcer bleeding. Further studies with a larger sample size are recommended.